Side‐Chain Engineering for Enhancing the Properties of Small Molecule Solar Cells: A Trade‐off Beyond Efficiency. Issue 14 (6th May 2016) - Min, Jie; Cui, Chaohua; Heumueller, Thomas; Fladischer, Stefanie; Cheng, Xiao; Spiecker, Erdmann; Li, Yongfang; Brabec, Christoph J.
Abstract : Three small molecules with different substituents on bithienyl‐benzo[1, 2‐b:4, 5‐b′]dithiophene (BDTT) units, BDTT‐TR ( meta ‐alkyl side chain), BDTT‐O‐TR ( meta ‐alkoxy), and BDTT‐S‐TR ( meta ‐alkylthio), are designed and synthesized for systematically elucidating their structure–property relationship in solution‐processed bulk heterojunction organic solar cells. Although all three molecules show similar molecular structures, thermal properties and optical band gaps, the introduction of meta ‐alkylthio‐BDTT as the central unit in the molecular backbone substantially results in a higher absorption coefficient, slightly lower highest occupied molecular orbital level and significantly more efficient and balanced charge transport property. The bridging atom in the meta ‐position to the side chain is found to impact the microstructure formation which is a subtle but decisive way: carrier recombination is suppressed due to a more balanced carrier mobility and BDTT based devices with the meta ‐alkylthio side chain (BDTT‐S‐TR) show a higher power conversion efficiency (PCE of 9.20%) as compared to the meta ‐alkoxy (PCE of 7.44% for BDTT‐TR) and meta ‐alkyl spacer (PCE of 6.50% for BDTT‐O‐TR). Density functional density calculations suggest only small variations in the torsion angle of the side chains, but the nature of the side chain linkage is further found to impact the thermal as well as the photostability of corresponding devices. The aim is to provide comprehensive insight into fine‐tuning the structure–property interrelationship of the BDTT material class as a function of side chain engineering. Abstract : A comprehensive insight into fine‐tuning the structure–property interrelationship (a trade‐off beyond efficiency) of the bithienyl‐benzo[1, 2‐b:4, 5‐b′]dithiophene material class as a function of side chain engineering is provided.